PLC Programming In Instruction List According To IEC 61131-3 A Systematic And Action-Oriented Introduction In Structured Programming - Adam, Hans-Joachim.; Adam, Mathias (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2022)
This textbook and exercise book provides a solid basic knowledge and comprehensive practical skills in dealing with PLC programming. Numerous exercises help to deepen the material. With the accompanying simulation software and sample solutions, the acquired knowledge can be applied immediately. The software can be downloaded via the Internet. The knowledge of number systems and digital technology conveyed in the book is an important prerequisite for skilful and clever PLC programming. The programming language used, "Instruction list according to IEC 61131-3", provides the best insights into the functioning of a PLC. The didactically prepared programming examples for switching networks, signal memories, time functions, counters, function blocks and functions, program structures, sequence controls, data types and much more enable systematic learning of programming. The 5th, corrected edition experiences an expansion of the exercises with a didactically prepared project for the control of a mountain railway. The associated simulation software "PLC-lite" enables the realisation of controls for the mountain railway and the "realistic" representation of the cableway movements on the screen. The content Number systems, dual numbers and codes.- Boolean algebra.- Flip-flops and static memories.- Dynamic memory elements and counters.- Switching networks with PLC.- Circuits with signal memories.- Time functions.- Counters.- Function blocks.- Jumps, loops and repetitions.- Functions.- Sequential controls. The target groups The book is intended for pupils, trainees and students of all technical disciplines or interested engineers. It is very well suited for self-study. The authors Dipl.-Ing. Hans-Joachim Adam studied electrical engineering and has been involved in education for over 20 years. Dipl.-Ing. Mathias Adam is a system consultant and specializes in compiler development for microcontrollers. This book is a translation of an original German edition. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.
Number systems, dual numbers and codes -- Boolean algebra -- Flip-flops and static memories -- Dynamic memory elements and counters -- Switching networks with PLC -- Circuits with signal memories -- Time functions -- Counters -- Function blocks -- Jumps, loops and repetitions -- Functions -- Sequential controls.
Keywords: Control engineering; Robotics; Automation; Computer programming; Control, Robotics, Automation; Programming Techniques